Analyzing the Sea Weather Effects to the Ship Maneuvering in Vietnam’s Sea from BinhThuan Province to Ca Mau Province Based on Fuzzy Control Method - Xuan Kien Dang; Le Anh-Hoang Ho; Viet-Dung Do (Universitas Ahmad Dahlan, 2018)
Vietnam is located in the tropical monsoon climate, so there are many storms affecting the marine environment each year. However, Vietnam’s sea also has distinct characteristics due to the continental shelf factors, salinity, sea currents and viscosity water. In this paper, the sea weather effects to the ship in the sea area from BinhThuan province to Ca Mau province are analyzed. Specifically, wave, wind and current which are the three main factors affecting the safety of ship are thoroughly examined. Importantly, the survey parameters have been built from the actual operating environment. In addition, maintaining the stability of dynamic positioning system in Vietnam weather conditions is the main point of this study.